TRADITIONS OF WELCOMING BIRTH IN THE ENDE COMMUNITY, EAST NUSA TENGGARA: THE DIALECTICS OF ISLAM AND LOCAL CULTURE - Hidayah, Hairul; Paris, Ilman (KOMUNITAS, 2023)
The tradition of welcoming a baby has an important role in the Ende people of East Nusa Tenggara.  This study aims to understand how religious and traditional aspects are dialectic in welcoming the birth of a baby. This research method uses an ethnographic approach, involving participatory observation, in-depth interviews with traditional and religious leaders, as well as literature studies to gain a comprehensive understanding of the traditional practices and Islamic values ??involved. The results of the study show that the tradition of welcoming babies in the Ende people is a blend of Islamic teachings and local cultural values. Religious aspects such as special prayers are integrated with local practices.. Despite social and religious changes, this tradition continues to function as a social glue and cultural identity for the Ende people.